Health of Elderly Parents, Their Children's Labor Supply, and the Role of Migrant Care Workers - Wolfgang Frimmel; Martin Halla; Jörg Paetzold; Julia Schmieder (Institute of Labor Economics (IZA), 2020)
We estimate the impact of parental health on adult children's labor market outcomes. We focus on health shocks which increase care dependency abruptly. Our estimation strategy exploits the variation in the timing of shocks across treated families. Empirical results based on Austrian administrative data show a significant negative impact on labor market activities of children. This effect is more pronounced for daughters and for children who live close to their parents. Further analyses suggest informal caregiving as the most likely mechanism. The effect is muted after a liberalization of the formal care market, which sharply increased the supply of foreign care workers.
Keywords: J14; J22; I11; I18; R23; 330; informal care; formal care; aging; health; labor supply; labor migration